Study on the Seismic Performance of Box-Plate Steel Structure Modular Unit - Hui Mao; Guang-chong Qin; Tao Lan (Advances in Materials Science and Engineering)
To study the seismic performance of the box-plate steel structure system, two three-storey single box-plate steel structure space stress-bearing unit test pieces have been designed and fabricated according to the 1 : 3 reduced scale. In addition, the quasi-static loading test has been performed on the test pieces where the destruction process, destroy mode, bearing capacity, hysteretic behavior, etc., have been studied and the impact of reinforcing measures with a corner or not on the seismic performance of test pieces has been mainly analyzed. The test results show that the destruction of the box-plate steel structure modular unit under the low cyclic loading effect starts with corner buckling and ends with corner wallboard tear. The test piece has excellent bearing capacity and energy dissipation; the corner reinforcing structure measure also has enhanced the seismic performance of the modular unit. Based on the test, we have taken finite element numerical simulation to the test pieces, compared the analysis result of the test with the finite element, and verified the effectiveness of the finite element analysis method. This paper designs four groups of 64 finite element model test pieces and discusses the influence law of the height-thickness ratio of the wallboard, flexibility coefficient of corner reinforcing structure rib, and axial compression ratio to the seismic performance of the modular unit. The results show that the bearing capacity of the test piece is decreased with the increase of axial compression ratio under the premise that the wallboard height-thickness ratio and flexibility coefficient of the corner reinforcing structure rib are certain. Based on the above analysis results, we have put forward the lateral force resistance calculation model of the reinforcing structure modular unit with or without corner.